Women in Leadership in Latin American Regionalism (2019)
This paper explores the role of women in leadership in Latin American Regionalism and, more specifically, the incorporation of gender commitments at the Community of Latin American and Caribbean States (celac), focusing on the case of the overlapping mandates, during the period 2011-2014, of three women in the Presidencies of Chile, Argentina and Brazil: Michelle Bachelet, Cristina Kirchner, and Dilma Rousseff, respectively. The paper draws on feminist approaches and the literature of women and leadership, and incorporates peculiarities pointed out in the literature of Latin American regionalism, such as weak institutions, presidential diplomacy, and active transnational advocacy networks. The main argument advanced is that the effect of women in leadership cannot be taken for granted as gender was not a priority during the governments of these presidents. The more diffuse commitment to human rights, which they all shared, as well as their symbolic empowerment effect might have strengthened the gender cause advanced by civil society and transnational advocacy networks.